Enhancement of growth, yield and lodging resistance of rice variety MR219 through silicon and paclobutrazol application - Dorairaj, Deivaseeno (2017)
Lodging which is the displacement of plant from its vertical position is a factor affecting rice yield. It could be minimized by increasing the strength of the culm. Silicon (Si) is associated with sturdiness and rigidity whereas paclobutrazol (PBZ) inhibits gibberellin synthesis thus halting internode elongation. To date, no comprehensive research has been carried out in Malaysia particularly on the role of Si in rice. Thus, Si and PBZ were utilized to reveal its effect on agronomic traits and lodging resistance in MR219. Silicon was applied at 0, 2, 4 and 6 g per pot at 56 DAS as topdressing on soil surface in the first screenhouse experiment. Number of tillers, spikelets per panicle, percentages of filled spikelets and effective tillers, weight per panicle, hardness, flag leaf area, chlorophyll content, Si and lignin content increased as the rate of Si increased. Silicon application of 4 g/pot increased and improved yield performance and lodging resistance. The next experiment resolved the best method and stage of Si application whereby plants treated with 4 g/pot of Si as topdressing on soil surface at reproductive stage improved yield and fiber contents. Number of tillers per pot, spikelets per panicle, percentage of filled spikelets, weight per panicle and Si content were highest in application at reproductive stage as topdressing followed by soil incorporation. Meanwhile, chlorophyll a content of topdressed and soil incorporated and flag leaf area of plants treated at reproductive stage as topdressing was the highest. Fiber contents of plants treated at reproductive and maturity stages as topdressing and soil incorporation were significantly higher. The third experiment combined Si with PBZ and tested six treatments: untreated, Si applied at 4 g and 6 g, PBZ applied at 400 mg/l, Si applied at 4 g and 6 g with PBZ 400mg/l. Silicon was applied as topdressing whereas PBZ as foliar at 57 DAS. Application of PBZ reduced plant height, culm length and flag leaf area but increased chlorophyll content. Percentage of filled spikeletes and weight per panicle of plants treated with Si or PBZ were significantly higher as compared to plants treated with combination of two factors. Silicon treated plants had significantly higher lignin and Si content. Cinnamyl alcohol dehydrogenase was up-regulated 3.4 fold in Si treated plants compared to others. Acidified phloroglucinol staining of leaf sample proved the presence of lignin with varying intensity. Hardness and brittleness was highest in plants treated with Si or PBZ. Scanning electron micrographs showed prominent deposition of trichomes, silica bodies, dumb-belled shaped or ladder like structures whereas X-ray spectra of leaf surface attest silicification of silica cells was more intensive in Si treated plants. In conclusion, Si enhanced yield components, reinforced cell structure and improved overall growth of rice plant. Farmers could use crop residues, such as rice husk ash, straw or rice hull as a cheaper alternative of Si source at the start of reproductive stage to maximize output. Amino acids such as glutamine and histidine, and Si solubilizers could be incorporated to increase Si uptake in rice plant.